Direct red 83 textile dye degradation using photoperoxidation and photo-fenton: kinetic studies, toxicity and neural networks modeling - Amorim, Nataly Daiany de Oliveira; Nascimento, Graziele Elisandra do; Charamba, Lívia Vieira Carlini; Santana, Rayany Magali da Rocha; Silva, Pollyanna Michelle da; Napoleão, Thiago Henrique; Napoleão, Daniella Carla (Ciência e Natura, 2020)
Textile dyes have been observed in aquatic matrices that receive effluents from different textile industries. These compounds have the peculiarity of being resistant to the physical, chemical and biological treatments commonly used in wastewater treatment plants. Thus, alternative treatments such as advanced oxidative processes (AOP) have been considered in order to promote the degradation of this type of pollutant, being the photoperoxidation and photo-Fenton processes the most used. Therefore, the present work evaluated the efficiency of these AOP in the degradation of direct red 83 dye. It was found a greater efficiency of the photoperoxidation process, especially in the degradation of functional groups observed at 289 nm. This AOP presented a pseudo first order reaction kinetics, with rapid decay in the first minutes. The MLP (5-21-2) neural network model was able to satisfactorily predict the degradation of the dye under study. Finally, it was found that the proposed process showed no adverse effects when studying the toxicity in bacteria.